FeF3-catalyzed MCR in PEG-400: ultrasound assisted synthesis of N-substituted 2-aminopyridines. Issue 71 (14th July 2016) - Kumar Reddy, Dinne Naresh; Chandrasekhar, Kothapalli Bannoth; Siva Ganesh, Yaddanapudi Sesha; Reddy, G. Rajeshwar; Kumar, J. Pradeep; Kapavarapu, Ravi Kumar; Pal, Manojit
Abstract : Ultrasound assisted 4-CR catalyzed by FeF3 afforded various N -substituted 2-aminopyridines as potential inhibitors of PDE4. Abstract : FeF3 catalyzed four component reaction under ultrasound irradiation was explored for the first time to prepare N -substituted 2-aminopyridines in good yields. The methodology involved the use of readily available starting materials and PEG-400 under mild reaction conditions in the presence of air. The one-pot methodology afforded a range of compounds of pharmacological interest indicating its potential in generating a diversity based library of small molecules useful for medicinal chemistry and drug discovery.